The effects of sleep duration on child health and development - Ha Trong Nguyen; Stephen R. Zubrick; Francis Mitrou (Global Labor Organization (GLO), 2022)
This paper studies the extent to which sleep duration causally affects health, cognitive and noncognitive development in children and adolescents. Using over 50 thousand time use diaries from two cohorts of Australian children spanning over 16 years, we first document that children sleep significantly less on days with longer daylight duration, partly by going to sleep later and waking up earlier. We then exploit variations in local daily daylight duration measured on predetermined diary dates across the same individuals through time as an instrument in an individual fixed effects regression model to draw causal estimates of sleep duration on a comprehensive set of child development indicators. Our results show that sleeping longer improves selected general developmental, behavioural and health outcomes in children and adolescents. By contrast, sleeping more statistically significantly increases their BMI scores, mainly by increasing the risk of being overweight. Moreover, while the impact of sleep duration on general and behavioural outcomes is more pronounced for females or older individuals, the effect on BMI is largely driven by males. The results indicate a null or relatively small positive impact of sleeping longer on cognitive skills.
Keywords: I00; I12; J22; J24; 330; Sleep; Time Allocation; Circadian Rhythms; Human Capital; Child Development